(untitled) (Ameghiniana, 2014)
Bird footprints recovered from the Anacleto Formation (Campanian, Upper Cretaceous) at Sierra Barrosa, northeast of Plaza Huincul, Neuquén Province, represent the earliest record s of bird traces from Patagonia. All of the specimens were recovered from two sites at the same stratigraphic level separated by less than a hundred meters. They are tridactylous, c1awed prints with divarications greater than 90° between digits II and IV, and seem to represent three different ichnotaxa. The most common avian footprint lacks hallux traces and can be referred to Aquatilavipes. A smaller number of the footprints includes distinct hallux impressions, and are similar to Ignotornis and Jindongornipes. The third type represents a new ichnotaxon, Barrosopus slobodai ichnogen. et ichnosp. nov. characterized by smaller size and a digit II impression that is separate from the conjoined third and fourth ones. These fossilized bird tracks are the first reported from the Neuquén Basin, and double the number of Cretaceous occurrences of avian footprints in Argentina.